Potential for Implementation of ePortfolios in a Western Australian Agribusiness Educational Program to Optimise Employability and Improve Transition from Student to Employee - Carter, Stacey Anne (Curtin University, 2024)
Agricultural degrees are multidisciplinary and nuanced, providing students opportunities to develop both core and highly individialised skills. Evidence indicates that ePortfolios are excellent tools to support students in multidisciplinary contexts with embedded individual learning journeys. This research explores Western Australian agricultural student and employer perceptions of student employability skills and subject knowledge, and makes recommendations on how ePorfolios can be embedded to address the tension between employer and student understanding and expectations of graduate skills.